IN THE CRADLE OF RUSSIAN PEDIATRICS (X - EARLY XVIII CENTURIES) - G.L. Mikirtichan; R.V. Suvorova ("Paediatrician" Publishers LLC, 2006)
The article outlines data on traditional folk «pediatrics» in Russia, covering attitude to children, ways of taking care for a child, means of treatment and prophylaxis of children's diseases. The article reviews the protosourses, investigating the treatment manuscripts kept in the national library of St. Peterburg: the treatment manuscript of the end of XVII century from the collection of Titov, the treatment manuscript of 1656, the grand home apotheque of Gurchin Daniil (1708); The Fresh Vertograd of the end of XVII - the beginning of XVIII centuries and others.Key words: children, history of medicine.